A collaborative halal supply chain model to address safety and transparency based on blockchain technology - Mahmod Attar Bashi, Zainab Senan; Khedher, Akram M Z M; Haque, Md Ihsanul; Hossen, Md Sazzad (Al Qasimia University., 2024)
Muslim spending on halal food is growing at 6.3%, projected to reach $2 trillion by 2024, raising concerns about the authenticity of halalclaims due to the inability to trace products throughout the supply chain. This research has two primary objectives: first, to develop a decentralized model for halal tracking using blockchain technology, and second, to assess Customers' awareness of blockchain applications in the halal industry. The proposed system uses blockchain's decentralized and immutable nature to record data transparently and securely, covering halal product origin, quality, handling, and processing. This will enhance supply chain transparency, improve record-keeping efficiency, strengthen food safety and quality assurance, and build consumer trust through end-to-end traceability. The development process involves smart contracts, cryptographic techniques, and data analytics, implemented using Ethereum 2.0 and Web3.js. Testing of the prototype system demonstrated strong scalability, handling high loads without compromising efficiency, and adhered closely to predefined guidelines, enhancing trust in the system’s reliability.